Evaluation of Medication Errors in Hospitalized Patients - Mosah, Hamoudi A.; Sahib, Ahmed S.; AL-Biati, Haedar A. (AL-Kindy College Medical Journal, 2012)
Objectives: Many medication errors occur in the hospital, and these can endanger patients. The purpose of this study was to evaluate the incidence of medication errors in hospitalized patients, and to categorize the most frequent types of errors, and to asses the possible measures that may prevent the occurrence of such errors.Methods: A prospective, exploratory, and evaluative study, using direct observation method to detect medication errors in adult hospitalized patients in medical and surgical units in Baquba Teaching Hospital- Diyala-Iraq.. The files of 299 patients had been reviewed from July 2009 to September 2009, including medication orders and treatment sheets to detect existing errors. The detected errors were recorded and classified using special form designed according to standard classification of medication errors.Results: During the study period, a total of 299 patient's files were reviewed and identified. The incidence of medication errors was 8.7%. The most common types of errors; where incorrect medication which includes 38.46% for not indicated drugs and 19.23% for drug-drug interaction. The incorrect dose represents the second common type of medication errors which include 15.38% for over dose and 3.85% for under dose. The classification of medication errors in this study were 61.54% prescribing errors, followed by 19.23% for each of dispensing errors and administration errors.Conclusions: Medication errors occur for a variety of reasons, including inaccurate communications and deficits in knowledge and performance by and among all health care professionals. In this study we addressed and identified that prescribing errors are the most common type of medication errors followed by dispensing and admintration types, so, all health care professionals have a responsibility in identifying contributing factors to medication errors and to use obtained information to reduce further error occurrence.